Secretory Leukocyte Protease Inhibitor Is an Inducible Antimicrobial Peptide Expressed in Staphylococcus aureus Endophthalmitis - Victor E. Reviglio; Ruben H. Sambuelli; Alejandra Olmedo; Micaela Falco; Jose Echenique; Terrence P. O'Brien; Irene C. Kuo (Mediators of Inflammation)
Purpose. To describe the presence of secretory leukocyte protease inhibitor (SLPI), a cationic peptide with antimicrobial and antiprotease activity, in the innate ocular immune reaction in a rat model of Staphylococcus aureus endophthalmitis. Methods. Seventy-five female Lewis rats were divided into three groups: the endophthalmitis group received an intravitreal injection of 65 colony-forming units of viable S. aureus, the vehicle-injected group received balanced sterile saline solution (BSS), and the control group was not injected. Eyes were enucleated at 24 and 48 hours and processed for immunohistochemical staining and Western blot studies for SLPI. Results. In S. aureus endophthalmitis eyes, there was strong immunostaining for SLPI in the retina and vitreous with associated neutrophilic infiltrates. At 48 hours, corneas also stained for SLPI. Western blots confirmed increased SLPI expression in all infected eyes. By immunohistochemical assays, SLPI was absent in the BSS and control eyes. The causative pathogen was identified in all samples from the endophthalmitis group by traditional culture methods. Conclusions. To our knowledge, this report is the first to demonstrate the presence of SLPI in the inflamed cornea, vitreous, and retina tissues of rat eyes with S. aureus endophthalmitis, suggesting that SLPI has an active role in the innate immunity of the eye. Release of SLPI by inflammatory cells in the anterior and posterior segments may contribute to the host defense response against infectious endophthalmitis.